Crossing Texts, References and Images. A Survey of a City Planner’s Personal Library in São Paulo (1920-1960) (1/2) - Heliana Angotti-Salgueiro (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The analysis of the intellectual path of an urban planner in São Paulo, Brazil, between the 1920s and the 1950s, is a subject that leads to little-studied issues in urban historiography: personal libraries, reference sources and appropriations. This is especially the case with visual representations of urban problems published in books and journals, particularly those from North America with broad international circulation during those years. A shared dimension of textual and visual documents in the history of transnational town planning from this period emerges in original analyses developed in two articles, composing a Dossier. Further, the particularity of this work is that it crosses biographical and bibliographical frameworks in a moment central to this history. The connections studied go beyond the peculiar case study to allow for the understanding of a cross-cultural flow of references in this key period of planning studies and visual representations of its issues.